Solution-processed ZnO/SnO2 bilayer ultraviolet phototransistor with high responsivity and fast photoresponse. Issue 22 (24th May 2018) - Choi, Hojoong; Seo, Sehun; Lee, Jong-Hoon; Hong, Sang-Hyun; Song, Jaesun; Kim, Seungkyu; Yim, Sang-Youp; Lee, Kwanghee; Park, Seong-Ju; Lee, Sanghan
Abstract : Enhanced UV photoresponse characteristics through insertion of a SnO2 carrier transport layer with high field effect mobility. Abstract : UV phototransistors based on ZnO, a material considered promising owing to its wide direct bandgap and high stability in harsh environments, have been intensively investigated. However, ZnO single-layer UV phototransistors, especially solution-processed devices, still exhibit poor electrical and UV photoresponse characteristics. Herein, we report the fabrication of a low-cost, large-area, and high-performance solution-processed ZnO/SnO2 bilayer UV phototransistor with improved electrical and UV photoresponse characteristics attained by inserting a SnO2 carrier transport layer, which is the actual path of the electrons. The photogenerated electrons are readily transferred from the ZnO UV-sensitive layer to the SnO2 carrier transport layer, owing to the lower conduction band of the SnO2 carrier transport layer than the ZnO UV-sensitive layer. In addition, the efficient extraction of photogenerated electrons from the ZnO UV-sensitive layer through the SnO2 carrier transport layer with high field effect mobility contributes to the improvement in the UV photoresponse characteristics of the ZnO/SnO2 bilayer UV phototransistor. The ZnO/SnO2 bilayer UV phototransistor exhibits high responsivity and detectivity as well as fast photoresponse. These results demonstrate that the solution-processed ZnO/SnO2 bilayer UV phototransistor developed in this study provides a novel approach for improving the performance of UV phototransistors with low-cost and large-area processing.